Records management and ISO 9000 / Prof. Dato' Dr. Raja Abdullah Yaacob - Yaacob, Raja Abdullah (Faculty of Information Management, 2009)
The quality standard in records management depends on proficiency not only in records management but also in the business operations that comprise the mission of the organization. In a quality environment, operating without a records management program could result in loss of business, erosion of customer confidence and non-compliance. Records are being neglected, ill managed and destroyed at an alarming rate. It is hoped that by incorporating quality in records management, proper procedures are abided and a quality document management system can be established in compliance with ISO 9000. This paper attempts to explore the importance of quality in records management and how quality can become part and parcel of records management program.